Education for Sustainable Development Oriented Didactic Design in A Bioplastic Context in Overcoming Barriers to Learning and Developing Attitude and Environmental Awareness - Alfira Julian Pratiwi*; Hernani Hernani; Budiman Anwar (Universitas Syiah Kuala, 2023)
Human ignorance in conserving, managing, and protecting the environment makes plastic pollution a real problem for the world's health and environment. Therefore, this study aims to develop environmental attitudes and awareness as well as mastery of pre-service teachers’ concepts through ESD-oriented didactic design in the context of bioplastics. This study used a Didactical Design Research (DDR) with 27 pre-service teachers. The instruments used in this study were tests, questionnaires, validation sheets, and transcripts. Based on the results of the analysis, it was found that there are attitudes and awareness of pre-service teachers that need to be developed, the results of preconception data analysis of pre-service teachers experienced learning barriers in content (1) classification of biodegradable biopolymers (2) starch decomposition process (3) benefits of biopolymers in various fields (4) and the environment (5) bioplastic dilemma (6) function of materials in the manufacture of bioplastics. The validation results indicate that improvements are needed in the learning objectives and some improvements in sentence redaction in didactic situations. After the learning was applied, it was found that most of the responses that emerged from the pre-service teacher were in accordance with what was designed by the educator, and after the percentage analysis was carried out there was a development of attitudes and awareness and mastery of concepts of the pre-service teacher.